DEVELOPMENT OF LANGUAGE AND ITS IMPLICATIONS ON LEARNING - Abdul Qadir Jaelani; Wardatul Asfiyah (STKIP PGRI Tulungagung, 2019)
Humans are social creatures that interact with each other. A language is a communication tool used to interact, every human development has a language development whose proportions are not the same. Starting with babies, children, adolescents to adults have different language development. And therefore the learning obtained is also different. How are language development and implications for development? In this paper use the library research. The result, the ability of language greatly affects the success of learning and cognitive development of children. Language facilitates teacher communication with students in teaching and learning activities. One of the factors that influence the success of learning is the effective use of language in every learning starting from planning, implementation, and assessment.